Aktualisasi Lima Pilar Manajemen Mutu Secara Sistematis Kepemimpinan Manajerial Kepala Sekolah - Yurman Zainal (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2022)
The principal's efforts to promote high quality schools have failed to live up to the expectations of our society. The principal's performance has not shown the best and most encouraging results. Without a doubt, this shortfall will have an impact on the quality of education in schools. The purpose of this study was to study the empirical description of leadership skills in the following areas: managerial leadership, vision, mission, and goals of the school, inculcation of school quality cultural values, implementation of programs and plans, and school quality control and control. In this study, the approach used to conduct research. The orientation of phenomenological techniques is the behavior and knowledge of school residents in school administration, as well as their interactions with other people, in order to improve school quality. Informants were chosen deliberately. Qualitative techniques are used in this study. In-depth interviews, participatory observations, and documentary studies were used to obtain the data. The data made several attempts using a triangular, member-check, and peer-check process. The findings in the research are, Principals have made efforts in their schools to foster a high-quality environment. Principals play an important role in implementing integrated quality TQM in the classroom. They do so according to instructions, and in their schools, power. - vision and mission of the company.